THE EFFECT OF DRILLING COMMUNICATION TECHNIQUE IN TEACHING STUDENTS’ PRONOUNCIATION AT SMA NEGERI 19 GOWA - Alfira, Nurfani; Rum, Eka Prabawati; Azis, Awalia (English Language Teaching Methodology, 2024)
The purpose of this study was to determine whether or not the use of the Drilling Communication Technique as a medium was effective in teaching students' pronunciation in the eleventh grade (SMA Negeri 19 Gowa in the academic year 2021/2022). This study used a pre-experimental design with pre-test and post-test designs. The comparison of pre-test and post-test scores is determined by the treatment outcome. The test was administered twice, once before and once after treatments or the teaching and learning process, using a recording tool.Based on the results of the study, the results of the data showed that there was a significant difference between the post-test and pre-test of students in the pre-experimental class. This increase is evidenced by the pre-test and post-test scores. From the post-test, the researcher found that the mean scores (72.88) were greater than the pre-test mean (46.22). It shows that there is a significant difference between the students' pre-test and post-test scores. According to the study's findings, Drilling Communication Technique could help students pronounce SMA Negeri 19 Gowa more accurately.